PENGARUH ROLE STRESS PADA TURNOVER INTENTIONS AUDITOR DENGAN KOMITMEN AFEKTIF SEBAGAI VARIABEL PEMODERASI - Sudarmawan, Putu Shaini Kusuma; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of role stress on turnover intentions, also to determine the ability of affective commitment to moderate the influence of role stress on turnover intentions. This research was done in Kantor Akuntan Publik were still active in Bali. This research using purposive sampling method. Methods of data collection using the survey, with a sample of 36 respondents. The analysis technique used is moderating regression analysis. This study shows that the role of stress a positive effect on turnover intentions. This study also showed that affective commitment is able to weaken the influence of role conflict and role overload on turnover intentions however not able to moderate the influence of role ambiguity on turnover intentions.
Keywords: role conflict, role ambiguity, role overload, role stress, turnover intentions, affective commitment